Food Powder Manufacture from Grape Pomace and its Application as an Improver in the Macaroni Production - Yavruyan, N. V.; Avetisyan, N. A. (ՀԱԱՀ հիմնադրամ)
A number of dietary and functional food products are manufactured by macaroni producing enterprises, which are presented in trade network, but their percentage ratio is still small. Nutritional and biological value of macaroni products can be enhanced due to the introduction of non-traditional raw materials and specific food additives in the recipe. Based on this, a concept for developing high quality and nutrient value macaroni production technology is recommended, which is related to the selection of nontraditional raw material. The novelty of the research is that the grape pomace powder is going to be used as an additive with high nutritional value.
Keywords: Food Science and Technology